Iron Supplement Consumption, Dietary Intake, Nutritional Status, and Anemia Among Adolescent Girls in Banawa, Donggala Regency - Nasrul, Nasrul; Hafid, Fahmi; Taqwin, Taqwin; Hikmah; Risma; Nuswantari, Atika; Sariman, Sarina (Media Publikasi Cendekia Indonesia, 2025)
This study aimed to examine the relationship between iron supplement consumption, dietary intake, nutritional status, and anemia among adolescent girls in Banawa, Donggala Regency. A cross-sectional analytical design was applied, involving 231 female students aged 12–15 years from SMP Negeri 3 and SMK Negeri 2 Banawa. Stratified sampling was used, and data were collected through interviews using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), anthropometric measurements, and hemoglobin testing via Point of Care Testing (POCT). Nutrient intake was assessed based on 80% adequacy of the Indonesian Recommended Dietary Allowance (RDA), while anemia was defined as hemoglobin levels <12 g/dL. Compliance with iron supplementation was determined using a median-based scoring method. The results revealed a high anemia prevalence (71.0%) among participants. Although 61.0% were compliant with iron supplementation, no significant association was found between supplement compliance and anemia status. Likewise, protein and iron intake showed no significant relationships. However, vitamin C intake was significantly associated with anemia (p = 0.001), indicating its crucial role in iron absorption. Nutritional status and iron inhibitor intake were not significantly related to anemia. The findings highlight the need for integrated school-based nutrition programs focusing on improving vitamin C intake and promoting effective iron supplementation practices.